Innovative agriculture and sustainable food production. Applications of the Aquaponics system - Giordano S. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
The present global scenario shows a twofold consumers’ behavior: on one hand, there is evidence of a growing demand for modern food; on the other one, it is easy to observe an increasing desire for natural foods. As far as innovations in the food industry are concerned, they often originate a lack of acceptance by the market, partly as a consequence of a phenomenon known as food neophobia; this involves the unwillingness to try new foods, as well as implies consumer reluctance with regard to emerging technologies in processing and producing food, known as food technology neophobia. As a consequence, in order to support marketing research, it is fundamental to analyse population segments that show food technology neophobic attitudes, as well as those groups regarded as early adopters of such innovative technologies. With reference to a specific application of the mentioned discourse, related to innovation in agriculture, the present contribution proposal aims at analyzing the potential of Aquaponics, defined as “the combination of aquaculture (raising fish) and hydroponics (the soil-less growing of plants) that grows fish and plants together in one integrated system”. This technology is considered at institutional level as “a resource efficient and environmentally friendly food production system”; aquaponics products are locally produced and attract an increased attention among consumers. The present contribution proposal will outline factors related to the mentioned food neophobia and applications of the Aquaponics system, responding to diverse ecological and social challenges related to efficient and sustainable forms of agricultural production. In particular, the case study of Agricoltura 2.0, in Italy, will be discussed as a best practice to reach relevant development objectives with specific reference to peri-urban areas.
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)